Pathogenic WDFY3 variants cause neurodevelopmental disorders and opposing effects on brain size - Le Duc, Diana; Kotzaeridou, Urania; Syrbe, Steffen; Driedger, Jan Henje; Ziegler, Andreas (Brain, 2019)
The autophagy scaffolding protein Wdfy3 helps regulate cortical size in mice. Le Duc et al. show that in humans, haploinsufficiency of WDFY3 leads to mild to mo